Burst capacity of reinforced thermoplastic pipes based on progressive failure criterion. (15th August 2021) - Wang, Yangyang; Lou, Min; Zeng, Xin; Dong, Wenyi; Wang, Sen
Abstract: This paper examines the burst capacity of reinforced thermoplastic pipes (RTPs) under the effect of internal pressure. Used the theory of the three-dimensional (3D) thick-walled cylinder, combined the 3D Hashin failure criterion with the theory of the evolution of damage in composite materials, considered the nonlinear stress-strain relationship of materials, and introduced changes in the winding angle caused by deformation to formulate a analytical model for the progressive failure analysis of RTPs. The model was used to examine the failure sequence and burst capacity of the RTPs, and analytical results agree well with the experimental ones. The results show that the ply number of the reinforced layer had a more significant effect on the burst capacity of the RTPs than the winding angle. Their burst capacity first increased and then decreased with increasing winding angle. When the winding angle was ±60°, the burst pressure reached its peak. With an increase in the ply number of the reinforced layers, the burst pressure of the RTPs increased nonlinearly and its rate of growth gradually decreased. Once a certain ply number in the reinforced layer had been reached, interlaminar separation was more likely to occur in the RTPs before they burst. Highlights: An analytical model is proposed to predict failure pressure of reinforced thermoplastic pipes (RTPs). The 3D thick-walled cylinder theory, combined the Hashin failure criterion is introduced to formulate the progressive failure analysis model. Considered the nonlinear stress-strain relationship of materials, and introduced changes in the winding angle caused by deformation. The accuracy of burst pressures calculated by the proposed model is verified by hydraulic burst tests.